2022
DOI: 10.3390/educsci12040245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of First-Time Experiences and Self-Regulation on College Students’ Online Learning Motivation: Based on a National Survey during COVID-19

Abstract: The COVID-19 pandemic has forced many college students in developing countries to engage in online learning for the first time, and the sudden transit has raised concerns regarding students’ competencies for, perception of, and attitude towards online learning. To address those concerns, this study measured three essential constructs of online learning (self-regulated learning, perceived presences, and learning motivation) based on a national survey in China (N = 12,826) and employed structural equation modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 79 publications
0
15
0
2
Order By: Relevance
“…At the beginning of COVID-19, students' knowledge of the limitations of online learning rose, and they devoted more emphasis to enhancing their capacity to self-regulate. In general, the early stage of the development of selfregulation can only reveal a change, not its extent or influence on students [18]. According to a new study, from Fall 2019 to Spring 2020, there was little or no influence on overall student involvement, despite the fact that a growing proportion of students modified their self-regulated learning strategies and plans [19].…”
Section: Early Stagementioning
confidence: 99%
“…At the beginning of COVID-19, students' knowledge of the limitations of online learning rose, and they devoted more emphasis to enhancing their capacity to self-regulate. In general, the early stage of the development of selfregulation can only reveal a change, not its extent or influence on students [18]. According to a new study, from Fall 2019 to Spring 2020, there was little or no influence on overall student involvement, despite the fact that a growing proportion of students modified their self-regulated learning strategies and plans [19].…”
Section: Early Stagementioning
confidence: 99%
“…For example, Hong et al ( 2021 ) found that university students with higher levels of self-regulation held positive views on the effectiveness of online learning experiences. Li et al ( 2022 ) found that SRL significantly predicted college students’ online learning behaviors and motivation. However, no existing study has so far investigated the relation between students’ SRL skills and their acceptance of online learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current study addressed this research gap by including these two important constructs in the same model to assess their relations and their effects on students’ participation in online learning. Third, most studies on online learning have been conducted among tertiary-level students (e.g., Aguilera-Hermida et al, 2021 ; Bol & Garner, 2011 ; Jansen et al, 2020 ; Li et al, 2022 ); this study, however, focused on secondary school students—who are less mature in terms of SRL and face more challenges in online learning—and on how their SRL skills and acceptance affect their participation in online learning.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers frequently express concerns regarding fractions as it is essential for algebraic thinking, proportional reasoning, advanced mathematics, and other science topics (Purnomo et al, 2021;Sidney et al, 2019). However, teaching and learning fractions are challenging for students (Li et al, 2022;Purnomo et al, 2019), prospective teachers (Baek et al, 2017;Rosli et al, 2020), and teachers (Copur-Gencturk, 2021;Putra, 2016). Without any underlying reasons, various mysterious rules have been presented in fractions teaching and learning.…”
mentioning
confidence: 99%